Histological analysis of the use of biphasic ceramics based on hydroxyapatite and β-tricalcium phosphate in maxillary sinus floor elevation surgery: pilot study - Luis Eduardo Marques PADOVAN; Diego GARCIA E SOUSA; Silvia Helena Marques PADOVAN; Guilherme José Pimentel LOPES DE OLIVEIRA; Ricarda Duarte da SILVA; Marcela CLAUDINO (Universidade Estadual Paulista, 2018)
Abstract Objective To evaluate the bone repair associated with the use of biphasic ceramics based on hydroxyapatite and β-tricalcium phosphate (HA/TCP) in the procedures of maxillary sinus membrane elevation in human beings. Material and method Ten patients with a residual bone ridge in the posterior maxillary region between 3 mm and 5 mm in height were selected and indicated for procedures of bone grafting associated with maxillary sinus lift procedure. The maxillary sinuses were filled with HA/TCP, and after 8 months, the implants were implanted and a bone biopsy was collected with the aid of a trephine drill, which was then submitted to histological analysis for the evaluation of the composition of the grafted area. Result The histological description analysis of the biopsies revealed the presence of vital and immature bone tissue, juxtaposed to the biomaterial. Histomorphometric analysis showed that the biopsy composition was in average 28.8%, 27.4%, and 43.6% of bone tissue, biomaterial, and soft tissue, respectively. Conclusion The areas grafted with HA/TCP presented the adequate amount of bone formation that allowed the implantation of the implants. The success of the grafting procedure with this biomaterial was associated with its osteoconduction potential that allowed the formation of bone tissue in close contact with HA/TCP.